Knowledge production and epistemic injustices: The use of digital technologies and artificial intelligence - Zermeño-Flores, Ana Isabel; Tufte, Thomas; Navarrete-Vega, Mabel Andrea (MedieKultur: Journal of media and communication research, 2024)
This article explores the complexities emerging from the knowing subject engaging in knowledge generation through artificial intelligence and digital technologies. By exploring a recent literature review as our case study, the possible existence of biases that may distort the studied reality and generate epistemic inequalities is investigated. A reflexive approach drawn from decolonial and feminist perspectives is applied. Findings underline the presence of epistemic biases, such as the invisibility of the knowing subject and knowledge representation, indicating that they are not simple isolated biases but part of a systemic problem that transcends specific scientific and technological practices. Ultimately, the complexity leading to epistemic biases is highlighted, encompassing interconnected systems, including the scientific, technological, and institutional.